Electrocardiographic Risk Markers of Cardiac Death: Gender Differences in the General Population - Haukilahti, Mira Anette E.; Kenttä, Tuomas V.; Tikkanen, Jani T.; Anttonen, Olli; Aro, Aapo L.; Kerola, Tuomas; Eranti, Antti; Holkeri, Arttu; Rissanen, Harri; Heliövaara, Markku; Knekt, Paul; Junttila, M. Juhani; et al. (Frontiers in Physiology, 2021)
Background: Cardiac death is one of the leading causes of death and sudden cardiac death (SCD) is estimated to cause approximately 50% of cardiac deaths. Men have a higher cardiac mortality than women. Consequently, the mechanisms and risk markers of cardiac mortality are not as well defined in women as they are in men. Aim: The aim of the study was to assess the prognostic value and possible gender differences of SCD risk markers of standard 12-lead electrocardiogram in three large general population samples. Methods: The standard 12-lead electrocardiographic (ECG) markers were analyzed from three different Finnish general population samples including total of 20,310 subjects (49.9% women, mean age 44.8 ± 8.7 years). The primary endpoint was cardiac death, and SCD and all-cause mortality were secondary endpoints. The interaction effect between women and men was assessed for each ECG variable. Results: During the follow-up (7.7 ± 1.2 years), a total of 883 deaths occurred (24.5% women, p<0.001). There were 296 cardiac deaths (13.9% women, p<0.001) and 149 SCDs (14.8% women, p<0.001). Among those who had died due to cardiac cause, women had more often a normal electrocardiogram compared to men (39.0% vs. 27.5%, p=0.132). After adjustments with common cardiovascular risk factors and the population sample, the following ECG variables predicted the primary endpoint in men: left ventricular hypertrophy (LVH) with strain pattern (p<0.001), QRS duration > 110 ms (p<0.001), inferior or lateral T-wave inversion (p<0.001) and inferolateral early repolarization (p=0.033). In women none of the variables remained significant predictors of cardiac death in multivariable analysis, but LVH, QTc ≥ 490 ms and T-wave inversions predicted SCD (p<0.047 and 0.033, respectively). In the interaction analysis, LVH (HR: 2.4; 95% CI: 1.2 - 4.9; p=0.014) was stronger predictor of primary endpoint in women than in men. Conclusion: Several standard ECG variables provide independent information on the risk of cardiac mortality in men but not in women. LVH and T-wave inversions predict SCD also in women.